Transcriptional silencing by the Polycomb protein in Drosophila embryos. - Muller, J. (The EMBO Journal, 1995)
Polycomb group (Pc-G) proteins act to keep homeotic genes stably and heritably silenced during Drosophila development. Here, it is shown that Polycomb (Pc), one of the Pc-G proteins, acts as a transcriptional silencer in Drosophila embryos if tethered to reporter genes by the DNA binding domain of GAL4 (i.e. as a GAL-Pc fusion protein). The results suggest that silencing by GAL-Pc requires the C-terminal portion of Pc, but not the chromodomain. If a pulse of Gal-Pc is provided, synthetic reporter genes are repressed, though only transiently. In contrast, reporter genes containing homeotic gene sequences remain stably and heritably silenced in a Pc-G gene-dependent fashion, even when GAL-Pc is no longer present. This implies that GAL-Pc recruits Pc-G proteins to DNA and suggests that maintenance of silencing requires the anchoring of Pc-G proteins to specific cis-regulatory sequences present in homeotic genes. The extent of DNA over which the Pc-G machinery acts is quite selective, as silencing established on one enhancer does not necessarily 'spread' to a juxtaposed synthetic enhancer.